Analisis Kemampuan Membuat Pola Rok Pias 6 Siswa Kelas X Tata Busana SMK Negeri 1 Beringin - Khaira, Annisa Ul; Widya, Intan; Gavrila, Zahra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The pias 6 skirt is a type of pias that has 6 pieces or pias. Pias skirt has several types such as skirt pias 2, skirt pias 5, skirt pias 6, skirt pias 7, and skirt pias 8. Students still feel difficulties in making pias skirt patterns 6 such as when measuring pattern sizes systematically, less skilled in the use of reading pattern signs such as the direction of pattern signs, pattern lines, use of various wrong pattern lines. In tracing the pias skirt pattern 6, the students were less capable in understanding pattern images. In placing the pattern on the material design it is still not precise and still does not match the fabric fiber, and is not correct in making the seam according to the instructions given. This research aims to determine the ability to make skirt patterns for 6 class X students Fashion Design at SMK Negeri 1 Beringin. This research was conducted in June 2018. The research location was at SMK Negeri 1 Banyan. The research is descriptive research. The population in this study was 48 students consists of 2 classes X. The sampling technique uses random sampling, namely 30 students in class X students. The data collection tool used was an observation sheet carried out by 5 observer whose grid consists of 19 indicators, scoring is determined with a value range of 4-1. Level the ability to make pias skirt patterns 6 in class X Fashion Design students at SMK Negeri 1 Beringin is at 79.80 and a standard deviation of 12.5 with the highest value of 93.5 and the lowest value of 56.5. from 30 samples. The research found that there were no very good results, 27 students (90%) obtained good results good, 2 students (310%) students got sufficient results and 1 student (3.33%) got poor results. This, it can be concluded that the students' ability to make pias skirt patterns is 6 in class X Fashion Design SMK Negeri 1 Beringin tends to be good.